Fourches patibulaires et corps suppliciés dans les enluminures des XIVe-XVe siècles - Cécile Voyer (Criminocorpus)
In the representations of the XIVe-XVe centuries, the figure of the forks, gibbets and hanged persons serve to define a society, a place where the order and the harmony are restored thanks to the exercise of a good justice. The trouble-maker is rejected to the margins of the society, the hanging – punishment of relegation – allows the society to find its cohesion after the exclusion of the criminal.Behind every image of hanged persons hides the figure of Judas, the archetypal traitor, sentenced to an endless death. That is why in the manuscripts of history, Chronicles, the social decay of the condemned person, the future damned soul, is clearly meant.